Case Report: Diagnosis and treatment of incontinentia pigmenti with central nervous system anomalies in one patient - Li, Yun; Hong, Junbin; Xu, Shangge; Zhou, Tong; Xiao, Xiaolan; Yang, Jinghua; Chen, Yiting (Frontiers in Pediatrics, 2025)
IntroductionThis article reports a detailed case of a patient with incontinentia pigmenti who exhibited epileptic status and dermatologic symptoms.Case presentationA 5-month-old female patient was brought to our hospital due to status epilepticus, with erythematous vesicular skin lesions on her trunk and extremities. Routine magnetic resonance imaging revealed infarction, ischemia, and encephalomalacia. Skin biopsy pathology indicated pigmentation disorder. Molecular genetic testing was conducted to identify IKBKG mutations, and the case was finally diagnosed with incontinentia pigmenti complicated by central nervous system anomalies. She was treated with oral levetiracetam (10 mg/kg/day, administered every 12 h) to control her recurrent seizures, and prednisone (1 mg/kg/day, once a day) for anti-inflammatory effects.ConclusionAfter nine months, her skin lesions have resolved, with only a few newly developed erythematous papules and areas of hyperpigmentation being evident. There were no recurrent epilepsy symptoms, developmental impairments, or other associated symptoms.